Hedge Funds vs. Private Equity Funds- Role as blockholders for shareholder’s value creation in the UK - Kala, Nitika (2015)
The purpose of our study is the differentiation in performance of the hedge fund and private equity funds targets in the United Kingdom. We take these two funds as our blockholders as they have the motivation, resources and ability to reduce agency costs and lead to its better or adverse performance. We analyse the reaction of the market by checking for abnormal returns around the date of the acquisition by any of the blockholder. To measure the short term effect, we conduct a short term event study and measure the long term effect by calculating and analysing the BHAR. We also test for the characteristics that attract a hedge fund or a private equity fund the most and ultimately leads to that firm being a target of either of the blockholders.